Digital Communication Strategy (International Scientific Conference Strategic Management and Decision Support Systems in Strategic Management, 2020)
Modern business conditions impose on companies an online presence as well as the application of digital marketing. Digital communication strategies, which are part of the overall marketing strategy, are also very important for digital marketing and are also integrated with the off line communication strategy. Any communication should be consistent with the basic message being sent, no matter whether it is implemented through traditional media or digital media. The great advantage of communicating through digital media is that the company can easily communicate with customers as well as develop strong relationships with them. It also easily collects data about them and stores them in databases creating the basis for precise targeting and sending of customized messages. Another advantage is that customers communicate, analyze, comment on the brand themselves, and thus create communities where they talk to each other, to the company and to attitude makers. This way companies are close to customers and follow what is said. This is especially important for social networks that are part of digital communication. When discussing the strategy of communication through social networks, there are several activities that are important for its realization. The first in a series is managing your reputation and defining a content strategy, followed by reach, action, conversion and ultimately engagement, that is, ongoing communication with customers. This paper will explain precisely these activities, as well as a closer definition of the digital communication strategy, with particular reference to social networks.